The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1074/jbc.m101866200
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide Enables Fas to Cap and Kill

Abstract: Recent studies suggest that trimerization of Fas is insufficient for apoptosis induction and indicate that super-aggregation of trimerized Fas might be prerequisite. For many cell surface receptors, cross-linking by multivalent ligands or antibodies induces their lateral segregation within the plasma membrane and co-localization into "caps" on one pole of the cell. In this study, we show that capping of Fas is essential for optimal function and that capping is ceramide-dependent. In Jurkat T lymphocytes and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
337
4
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 367 publications
(353 citation statements)
references
References 63 publications
(86 reference statements)
10
337
4
2
Order By: Relevance
“…found an association between ceramide C18:0 and depressive symptom severity in their study population (Demirkan et al., 2013). Importantly, both species have been implicated in apoptosis (Babenko, Hassouneh, Budvytiene, Liesiene, & Geilen, 2010; Cremesti et al., 2001; Grassme et al., 2001; Senkal et al., 2007; Thomas, Matsko, Lotze, & Amoscato, 1999). For ceramide C16:0, concentrations were found to be elevated in apoptotic cells within 2 hr of being exposed to ionizing radiation (Thomas et al., 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…found an association between ceramide C18:0 and depressive symptom severity in their study population (Demirkan et al., 2013). Importantly, both species have been implicated in apoptosis (Babenko, Hassouneh, Budvytiene, Liesiene, & Geilen, 2010; Cremesti et al., 2001; Grassme et al., 2001; Senkal et al., 2007; Thomas, Matsko, Lotze, & Amoscato, 1999). For ceramide C16:0, concentrations were found to be elevated in apoptotic cells within 2 hr of being exposed to ionizing radiation (Thomas et al., 1999).…”
Section: Discussionmentioning
confidence: 99%
“…For ceramide C16:0, concentrations were found to be elevated in apoptotic cells within 2 hr of being exposed to ionizing radiation (Thomas et al., 1999). Moreover, C16:0 has been shown to be required for the initiation of Fas‐induced apoptosis and may act as a second messenger after Fas ligation by inducing Ras activation and subsequent apoptosis (Cremesti et al., 2001; Grassme et al., 2001; Gulbins et al., 1995). C18:0 has been observed to induce apoptosis of keratinocytes in a concentration‐dependent manner (Babenko et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Other receptors, for instance CD95 or DR5, or infections with P. aeruginosa trigger a translocation of the acid sphingomyelinase onto the extracellular leaflet [39, 40, 43]. Translocation of the enzyme onto the outer leaflet of the cell membrane is very likely mediated by the fusion of vesicles, in particular secretory lysosomes that contain the enzyme [76], with the plasma membrane.…”
Section: Sphingomyelinasesmentioning
confidence: 99%
“…Several studies indicated that rafts are required to cluster CD95 and to recruit FADD, caspase 8 and 3 to CD95 upon stimulation (Grassme et al, 2001bHueber et al, 2002;Scheel-Toellner et al, 2002;Delmas et al, 2003;Aouad et al, 2004;Eramo et al, 2004). Accordingly, disruption of rafts prevented CD95-induced apoptosis, at least in most cells (Grassme et al, 2001b;Cremesti et al, 2001;Hueber et al, 2002;Scheel-Toellner et al, 2002). Likewise, a recent study by Delmas et al (2004) reported that DR4 and DR5 translocate into rafts upon stimulation.…”
Section: Introductionmentioning
confidence: 96%
“…For instance, the extracellular domain of CD95 contains a motif, the PLAD domain that mediates trimerization of CD95 and seems to contribute to the specificity of the interaction between CD95 ligand and CD95 . However, trimerization of the CD95 receptor is not sufficient to induce apoptosis (Schneider et al, 1998) and several studies demonstrated that CD95 signaling is initiated by oligomerization and aggregation (clustering), respectively, of the receptor in distinct domains of the cell membrane (Cremesti et al, 2001;Grassme et al, 2001a, b).…”
Section: Introductionmentioning
confidence: 99%